1997
DOI: 10.1088/0029-5515/37/8/i05
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of etaimode by reactive and dissipative descriptions and the effects of magnetic q and negative shear on the transport

Abstract: Ion temperature gradient driven modes are studied in the short wavelength region by using a three pole reactive fluid model and an adiabatic E X B convection model, as well as the gyro-Landau fluid model. In all of the above models the parallel ion dynamics is included and the results have been compared both analytically and numerically. Furthermore, the effects of the magnetic safety factor q on the growth rate and transport coefficient xi have been investigated. The maximum of xi as a function of the mode nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 46 publications
3
63
1
Order By: Relevance
“…The trend is seen in Ref. 11, although finite b effects are absent there. With our choice of parameters (similar to the Cyclone DIII-D case 36 ), the acoustic mode (not being sensitive to g i ) weakens the pure g i mode.…”
Section: Introductionsupporting
confidence: 60%
See 3 more Smart Citations
“…The trend is seen in Ref. 11, although finite b effects are absent there. With our choice of parameters (similar to the Cyclone DIII-D case 36 ), the acoustic mode (not being sensitive to g i ) weakens the pure g i mode.…”
Section: Introductionsupporting
confidence: 60%
“…The ion Landau resonance is taken into account in our model by adapting the Landau part of a gyro-Landau fluid model. 11,[26][27][28] It is shown that this complement (glf) may enhance the g i stabilization but otherwise that it gives growth, frequency, and ballooning properties which are similar to the case without ion Landau resonance being taken into account. The stabilization of the pure ITG mode with decreasing…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10,11 After extensive rearranging of terms we obtain 1. This term is in better agreement with kinetic theory in an expansion in FLR and magnetic drift 11 but complicates the eigenvalue equation considerably.…”
Section: Formulationmentioning
confidence: 99%